Medically Important Hemiptera: Bed Bugs and Kissing Bugs in Human Health. - Atul Khajuria1; Ashish Kumar 2; Prabhdeep Singh (International Journal of Insects, 2026)
Bed bugs (family Cimicidae) and kissing bugs (subfamily Triatominae) are hematophagous Hemiptera of major medical importance, yet they differ markedly in their public health impact. Bed bugs have resurged globally over the past three decades, with infestations reported from homes, multi-unit housing, hotels, transportation, and healthcare facilities in both high and low-income settings. They are not established biological vectors of human pathogens, but their bites cause pruritic papules, urticarial, and bullous reactions, occasional systemic allergic responses, and are strongly associated with anxiety, insomnia, stigma, and substantial economic burden from control costs, lost productivity, and housing disruption. Their biology—hemimetabolous development, obligatory blood feeding in all mobile stages, cryptic nocturnal behavior, and the ability of adults to survive months without feeding—favours persistence and makes eradication challenging, particularly in resource-constrained environments. Kissing bugs, in contrast, are proven vectors of Trypanosoma cruzi and are central to the transmission of Chagas disease in Latin America and, increasingly, in non-endemic regions through migration and non-vectorial routes such as transfusion and transplantation. They occupy domestic, peridomestic, and sylvatic ecotopes and feed on a wide range of mammalian reservoirs, embedding Chagas disease within complex zoonotic cycles. This review synthesizes current knowledge on taxonomy, morphology, life cycle, and host interactions of bed bugs and kissing bugs; the epidemiology and clinical features of bed bug infestation and Chagas disease; and the principles of diagnosis, management, and control.For bed bugs, emphasis is placed on clinical recognition of bite reactions, mental health consequences, and integrated pest management incorporating inspection, physical measures, and insecticide use in the context of widespread resistance.[2,5,15,16] For kissing bugs, the review highlights the pathogenesis and staging of acute and chronic Chagas disease, current diagnostic algorithms based on parasitological, serologic, and molecular methods, and the role of trypanocidal therapy alongside vector control, housing improvement, and blood safety measures. The article concludes by underscoring the need for coordinated clinical, environmental, and policy responses to mitigate the growing burden of bed bugs and to consolidate gains in Chagas disease control and elimination.
Keywords: Keywords: Bed bugs, Cimicidae; Kissing bugs, Triatominae, Chagas disease, Vector-borne disease, Bed bug infestation, Integrated pest management, Insecticide resistance, One Health